Soil analysis of Rhizospher Mangrove Rhizophora Sp East Bintuni Village - Sombo, Debora; Mogea, Rina Anita; Massora, Maria (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to examine the physical and chemical conditions of the soil in the rhizosphere of Rhizophora sp. mangroves in East Bintuni Village. The soil samples were collected from two locations, namely, the Rhizopora mangrove around the central market and the mangrove forest on Jalan Nusantara. The results of the laboratory analysis showed that the soil of the Mangrove Mangrove Around the Central Market has a soil texture of 3.75%; dust 54.80%; clay 41.45% so that based on the soil texture triangle by the United States Department of Agriculture (USDA), it belongs to the Silty clay class. The C-organic value of mangrove soil around the market was 5.90% and the archipelago mangrove forests were 5.12% in the very high category. The pH value of the Rhisphere mangrove is 2.95, and the pH value is 3.82, both locations of the pH criteria were very acidic. The Al and Fe values of the RH mangrove are very high (22.86 cmol/kg) and the C-Organic value is very low (39.6 and 41.1, respectively) while the CEC value is medium (18.8 and 41.2, respectively). The results could inform conservation and management practices, helping to preserve and restore mangrove habitats in the region and potentially guiding similar efforts in other coastal areas. In addition, research could examine the long-term effects of these soil conditions on mangrove ecosystems' ability to provide critical ecological services, such as carbon sequestration and coastal protection.